KEBIJAKAN LUAR NEGERI INDONESIA MENGHENTIKAN KERJASAMA PERTAHANAN SEMENTARA DENGAN AUSTRALIA TAHUN 2016 (STUDI KASUS: JOINT TRAINING AND MILITARY OPERATION INDONESIAN ARMED FORCES DAN AUSTRALIAN DEFENSE FORCES) - Juli Fetra Alfin; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this research is to understand This research will discuss about why Indonesian stopping defense cooperation temporary against Australian. In the last 2016, Indonesian Government based Ministry of Defense agree to stop defense cooperation against Australian. It is between Indonesian Armed Forces by Kopasus and Australian Defense Forces, both Joint training, joint military operation temporary stopped as a respon to an issue of humiliate of Pancasila by Australian Defense Forces. This research theoretically has built with Realism perspectives on International Relations and supported by Foreign Policy theory of James N.Rossenau. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems. Researcher has formulated answered-hypothesis whic reveals the fact that Indonesian foreign policy that stopping a defense cooperation temporary just caused by a bad relation between countries that always on conflict. It is caused a confidence building measure too. There is nothing a mutual trust each other. Australy been always look Indonesia as a threat from North. So, that’s make sense when Australy was always countering Indonesia as a threat not a companion. Keywords : Foreign Policy, Indonesia, Australia, Defense Cooperation, Joint Training, Joint Military Operation, Indonesian Armed Forces, Australian Defense Forces